Dry Needling for Arthrogenic Muscle Inhibition of Quadriceps Femoris in Patients after Reconstruction of Anterior Cruciate Ligament: a Protocol for a Randomized Controlled Trial - Milad Zarrin; Noureddin Nakhostin Ansari; Soofia Naghdi; Scott Hasson; Bijan Forogh; Mehdi Rezaee (Medical Association of Pharmacopuncture Institute, 2023)
Background : Dry needling (DN) is recommended as a therapeutic modality for various neuromusculoskeletal disorders. No study has been performed on the impact of DN on arthrogenic muscle inhibition (AMI) after anterior cruciate ligament reconstruction (ACLR). This study protocol is aimed to investigate the impacts of DN on AMI of quadriceps femoris, corticomotor, and spinal reflex excitability in patients with ACLR. Methods : A double-blind, between-subject, randomized, controlled trial will be conducted to measure changes in AMI after DN. Twenty-four subjects with ACLR will be recruited to receive a DN or a sham DN, providing that they met the inclusion criteria. Three sessions of DN on the quadriceps femoris will be applied during a one-week period. The primary outcome measures are the active motor threshold, motor evoked potential, and Hmax - Mmax ratio. The secondary outcomes are the International Knee Documentation Committee subjective knee form questionnaire score and maximum quadriceps isometric torque. Data will be collected at baseline, immediately after the first session, after the third session, and at the one-month follow-up visit. Discussion: The results of this study will provide preliminary evidence regarding the effects of DN on AMI of quadriceps femoris in patients with ACLR.